(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The purpose of the research is a comparative analysis of competitiveness of destinations of Crimea and Turkey by radar charts. Achievement of the set goal has been reached by accomplishment of the following tasks: conditions of development of tourism in the Crimea and Turkey were analyzed; the sequence of the method of radar charts was described; assessment indicators were selected; on their basis competitiveness was evaluated. The results can be used to develop measures aimed at improving the competitiveness of the Crimea destinations.